The surface density gradient of grafted poly (ethylene glycol): preparation, characterization and protein adsorption - Lin, Y.S. (1994)
A surface density gradient of grafted poly (ethylene glycol) (PEG) chains was prepared using two-phase silanization of a flat silica surface. The first step was to create the surface density gradient of isocyanatopropyldimethylsilyl groups and to hydrolyze the isocyanato moiety into an amine. These surface amines were reacted with an excess of aldehyde-terminated PEG. The PEG–silica surface was characterized by dynamic contact angle measurements, X-ray photoelectron spectroscopy and ellipsometry. The length of the PEG gradient region was approximately 7 mm and the thickness in air ranged from zero to 1.1 nm. The maximum surface density of the PEG layer, as calculated from ellipsometric data, amounted to an average 0.4 PEG (molecular weight M(w) = 2000 Da) molecule nm(−2), while the surface density average of the amine groups was 1.4 molecules nm(−2), indicating that only a fraction of the surface amines reacted with aldehyde-terminated PEG. The PEG segment density profile in the gradient PEG region was computed by a self-consistent mean field theory. The PEG (M(w) = 2000 Da) segments profile was not parabolic, but showed a thin depletion zone next to the surface. The influence of the surface density of the grafted PEG chains on protein repellence was tested by the adsorption of fibrinogen from solution and from a ternary protein solution mixture containing fibrinogen, albumin and immunoglobulin G. Fibrinogen adsorption onto the silica end of the gradient was extremely low, both in the presence of the other two proteins and in their absence. As the surface density of the grafted PEG chains increased, so did the fibrinogen adsorption (up to 0.024 μg cm(−2)). It is not clear whether this low fibrinogen adsorption resulted from the interactions of the protein with the grafted PEG chains or with residual surface amines that were available due to some imperfections in the grafted PEG layer.